FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS DI RSUD RADEN MATTAHER PROVINSI JAMBI - Erik Rosadi; Fithriyani Fithriyani; Muhammad Hidayat (Jurnal Akademika Baiturrahim Jambi, 2019)
Abortion is the cessation of pregnancy before the fetus be able to live outside the womb at less than 28 weeks of age, because most miscarriages are unknown and occur spontaneously. Factors that can cause of abortion are hypertension in pregnancy, anemia in pregnancy and the age of pregnant mother. This study aimed to determine the factor related to abortion at Raden Mattaher hospital Jambi province. This study was conducted on July 10 – 24, 2019 with total samples were 87 people. Sample used simple random sampling. The instrument used observation. Data analysed by using chi square test with a significance level () = 0.1 result of this study about the correlation of hypertension history in pregnancy with abortion indicated that ( p value = 0.209) it means that there is no correlation of hypertension history in pregnancy with abortion and there is anemia in pregnancy with abortion ( p value = 0.000), and the age of pregnant mother with abortion ( p value = 0.005) it means that there is the correlation of anemia in pregnancy and the age of pregnant mother with abortion at Raden Mattaher hospital Jambi province. It is concluded that there is no correlation between hypertension history in pregnancy with abortion and there is correlation between anemia in pregnancy and the age of pregnant mother with abortion